2007
DOI: 10.1016/j.jpainsymman.2006.09.030
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care in Hospital: Current Practice and Potentials for Improvement

Abstract: From July until September 2004, all deaths were registered prospectively in all departments of Freiburg University Hospital, Germany, a large teaching hospital with approximately 55,000 inpatient admissions per year. A retrospective chart review was done for all patients who died during this time period using a tool validated in two American and Australian projects. Main outcome measures were patients' identification as dying by medical staff, Do-Not-Resuscitate (DNR) orders, and the presence of comfort care p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 17 publications
2
29
2
1
Order By: Relevance
“…However, they often fail to broach the subject with the ill denying them a prescription for adequate relief of symptoms. (9,20) The same was true for this study. It is important to mention that many physicians do not optimize hospice care, mainly pain control, fearing a possible side effect of sedation analgesia drugs.…”
Section: Discussionsupporting
confidence: 74%
“…However, they often fail to broach the subject with the ill denying them a prescription for adequate relief of symptoms. (9,20) The same was true for this study. It is important to mention that many physicians do not optimize hospice care, mainly pain control, fearing a possible side effect of sedation analgesia drugs.…”
Section: Discussionsupporting
confidence: 74%
“…The order protocol aims to overcome many of the barriers to implementation of comfort care including lack of knowledge, inexperience, and discomfort with end-of-life opiate administration. 6,7,[9][10][11][12][13]24,25 The ESMO protocol delineates the patient criteria for use of the protocol, which include: (1) a plan not to resuscitate the patient, (2) the patient has a terminal illness, (3) the patient is experiencing symptoms such as uncontrolled pain or dyspnea for which opiate medications are an accepted treatment, and (4) the goals of treatment have been discussed with patient and/or surrogate. A section of the order protocol guides ordering an opiate continuous infusion aimed at symptom control, including suggested dosing parameters and guidelines for documenting titration for unrelieved symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…8 Even when clinicians and patients and their families recognize that a patient is nearing death and the goals of care should be reoriented toward the end of life, the shift in care may not proceed. 9,10 A medical record review of patients who died in the Study to Understand Prognosis and Preferences for Outcomes and Risks of Treatment (SUPPORT) found that approximately half had dyspnea and half had pain in the last 2 days, but patients with care aimed at comfort measures did not have statistically significantly better symptom management. 9 Furthermore, a retrospective study by Parish et al 11 found through case note auditing and key staff interviews that there was a lack of appropriate assessment and documentation of physical and psychosocial care in the inpatient setting toward the end of life.…”
Section: Introduction Wmentioning
confidence: 99%
“…In Australia, Canada, Sweden, and USA, a study revealed that the DNR rate order among 15 ICUs was 11% [11]. Approximately 60-70% of the patients who have DNR consent are those receiving palliative care in USA and Germany [12]. More surprisingly, a study reported that 72% of Finnish physicians discussing the DNR with the patients whom able to communicate [13].…”
Section: Prevalence Of Dnr Throughout the Worldmentioning
confidence: 99%